Discovery of tetrasubstituted pyrazines as semiochemicals in a sexually deceptive orchid - Bohman, B.; Jeffares, L.; Flematti, G.; Byrne, L.; Skelton, B.; Phillips, R.; Dixon, Kingsley; Peakall, R.; Barrow, R. (2012)
Sexually deceptive orchids employ mimicry of insect sex pheromones to exploit a diverse group of pollinators. The chemical structures of five semiochemicals (1-3, 7, 8) produced by populations of the warty hammer orchid, Drakaea livida, pollinated by a thynnine wasp in the genus Catocheilus were elucidated. With the exception of (2,5-dimethylpyrazin-3-yl)methyl 3-methylbutanoate (7), all active compounds were tetrasubstituted pyrazines, including hydroxymethyl (1) and ester (2 and 3) trimethylpyrazine derivatives. Male Catocheilus wasps were responsive to all of these compounds in GC-EAD experiments.